Association between Carbohydrate, Vitamin C, Vitamin E, and HBA1C Level - Andarwati, Dwi Astuti Dian; Murti, Bhisma; Sulaeman, Endang Sutisna (Indonesian Journal of Medicine, 2019)
Background: Diabetes is now a disease that is a major concern both globally and regionally and is the leading cause of death in most countries. HbA1c levels are used to measure long-term glucose levels in patients with type 1 and 2 Diabetes Mellitus (DM). Restrictions on carbohydrate diets have the greatest effect on decreasing blood glucose levels. Nutritional interventions with the provision of vitamin C and vitamin E can reduce inflammation and oxidative stress as a strategy to prevent the occurrence of DM. The purpose of this study was to determine the relationship of carbohydrate intake, vitamin C and vitamin E with HbA1c levels.Subjects and Method: This was a cross-sectional study conducted at Prodia Surakarta Clinic, Surakarta, Central Java, Indonesia. A sample of 150 study subjects was selected by fixed disease sampling. The dependent variable was HbA1c level. The independent variables were carbohydrate and vitamin E. The data were collected by questionnaire and 24-hour food recall. The data were analyzed by multiple logistic regression.Results: High carbohydrate intake increased HbA1c level (OR= 2.84; 95% CI= 0.72 to 11.12; p= 0.133), while high intake of vitamin E lowered HbA1c level (OR= 0.12; 95% CI= 0.02 to 0.64; p = 0.012).Conclusion: High carbohydrate intake increases HbA1c level, while high intake of vitamin E decreases HbA1c level.Keywords: diabetes, HbA1c, karbohidrat,  vitamin C.Vitamin ECorrespondence: Dwi Astuti Dian Andarwati. Masters Program in Nutrition, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: dianandarwati@yahoo.com. Mobile: 081329588344.Indonesian Journal of Medicine (2019), 4(3): 219-227https://doi.org/10.26911/theijmed.2019.04.03.04